2007
DOI: 10.1096/fj.06-6505com
|View full text |Cite
|
Sign up to set email alerts
|

19 F magnetic resonance imaging for stem/progenitor cell tracking with multiple unique perfluorocarbon nanobeacons

Abstract: MRI has been employed to elucidate the migratory behavior of stem/progenitor cells noninvasively in vivo with traditional proton (1H) imaging of iron oxide nanoparticle-labeled cells. Alternatively, we demonstrate that fluorine (19F) MRI of cells labeled with different types of liquid perfluorocarbon (PFC) nanoparticles produces unique and sensitive cell markers distinct from any tissue background signal. To define the utility for cell tracking, mononuclear cells harvested from human umbilical cord blood were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
284
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(297 citation statements)
references
References 35 publications
8
284
1
Order By: Relevance
“…It has already been demonstrated that bSSFP is the most SNR efficient pulse sequence in use. 30 Proof of principle that bSSFP was advantageous for the detection of 19 F-labeled stem cells has been previously reported by Partlow et al 31 In this paper, a liquid PFC was developed and used to label stem/ progenitor cells in culture. A single mouse then received an IM injection of 4 million fixed PFC-labeled cells and was imaged after euthanasia at 1.5 T with 2D bSSFP.…”
Section: Cell Detection With Bssfpmentioning
confidence: 76%
See 1 more Smart Citation
“…It has already been demonstrated that bSSFP is the most SNR efficient pulse sequence in use. 30 Proof of principle that bSSFP was advantageous for the detection of 19 F-labeled stem cells has been previously reported by Partlow et al 31 In this paper, a liquid PFC was developed and used to label stem/ progenitor cells in culture. A single mouse then received an IM injection of 4 million fixed PFC-labeled cells and was imaged after euthanasia at 1.5 T with 2D bSSFP.…”
Section: Cell Detection With Bssfpmentioning
confidence: 76%
“…For example, Partlow et al injected and detected 4 million cells in 50 µL at 1.5 T ex vivo. 31 The voxel size was 2.5×2.5×35 mm (∼220 µL); therefore, they detected 4 million cells in a voxel. They did this in a far shorter imaging time of 7 minutes compared to our 40 minutes.…”
Section: Cell Detection With Bssfpmentioning
confidence: 99%
“…[84][85][86] Additionally, in vivo perfluorocarbon emulsion infusion followed by 19 F MRI has been shown to preferentially detect areas of inflammation both in the CNS and systemically via preferential uptake by CD68+ macrophages, providing a non-invasive measure of disease activity in murine models of inflammatory disease. [87][88][89][90] Thus, the advantage of these labelling modalities includes the ability to directly visualise (and potentially in an EAE mouse model in which human MSCs engineered to express a myelin oligodendrocyte glycoprotein-specific receptor were intranasally delivered and found to significantly improve EAE symptoms better than non-engineered human MSCs, and prevented further EAE induction.…”
Section: Dmd = Disease-modifying Drug; Ipsc = Induced Pluripotent Stementioning
confidence: 99%
“…MRI and magnetic resonance spectroscopy are common imaging modalities for in vivo stem cell tracking in both preclinical and clinical settings (Hoehn, Kustermann et al 2002;Modo, Cash et al 2002;van den Bos, Wagner et al 2003;Kustermann, Roell et al 2005;Crowder, Brant et al 2006;Jansen, Shamblott et al 2006;Au, Lam et al 2007;Hsiao, Tai et al 2007;Magnitsky, Walton et al 2007;Partlow, Chen et al 2007;Politi, Bacigaluppi et al 2007;Suzuki, Cunningham et al 2007;Dash, Chan et al 2008;Himmelreich and Hoehn 2008;Kim and Song 2008;Terrovitis, Stuber et al 2008;Wu, Hu et al 2008;Kedzioreik, Ouwerkerk et al 2009;Kim, Huh et al 2009;Lythgoe 2009;Reekmans, Tambuyzer et al 2009;Solanky, Chung et al 2010;Tseng, Shih et al 2010;Chien, Hsiao et al 2011). Extraordinary three dimensional and anatomic resolution and high safety profile are the main advantages.…”
Section: Mrimentioning
confidence: 99%